Depicting reflections of power on illocutionary acts of Japanese Prime Minister ShinzÅ Abeâ€™s speeches on Covid-19 - Diana Kartika; R. Kunjana Rahardi; M. Aziz; Wahyudi Rahmat (Indonesian Journal of Applied Linguistics, 2023)
Speeches are often construed to exert oneâ€™s power while projecting a political intent towards the audience. This research examines how power is reflected in speeches by ShinzÅ Abe, a former Prime Minister of Japan, through the categorisation of speech acts. The speeches were delivered in many of his press conferences during the Covid-19 pandemic. The research employed a quantitative approach, and the analysis largely drew on Searle's classification of speech acts to identify and categorise Mr Abeâ€™s expressions of power. Data for this study focused on various formal press briefings, interviews, or other communicative exchanges he conducted in his role as a prime minister. Eight texts were selected for the analysis, and they were collected from the website of the Japanese Prime Minister's Secretariat office from February to May 2020. Findings from the analysis indicated that the prime minister mostly utilised performative verb utterance directions, such as informing (66%), asking (78%), promising (90%), thanking (54%), and deciding (76%), in a form of polite and respectful language, Keigo, to demonstrate reverence towards diplomatic entities. In addition, he frequently highlighted statistical data regarding the circumstances and the prevailing factors of the pandemic that led to a regime of truth and knowledge about Covid-19 in Japan. The findings provided better understanding of ShinzÅ Abeâ€™s exercise of authority in managing the variability of Covid-19 incidences in Japan, as reflected in the movement of relations with the society and with those diplomatic entities. This suggests that Shinzo Abeâ€™s speeches during the pandemic have a potential pathway that world leaders, linguists or students can traverse and inquire into to ensure community resilience to counteract the fragility caused by a pandemic.Â